Tingkat Kebugaran Jasmani Siswa Ekstrakurikuler Olahraga di SMA Negeri 1 Surade - Herlan Herlan; Rhama Nurwansyah; Rekha Ratri Julianti (Universitas Singaperbangsa, 2021)
The purpose of this study was to determine the results of the physical fitness level of extracurricular students at SMAN 1 Surade, whether they were in the good or poor category. The subjects in this study were all members of the sports extracurricular activities at SMAN 1 Surade with 23 students as respondents. The data collection technique used in this research is descriptive quantitative research. The method used was a survey, while the data collection technique used tests, the results of the study showed that the level of physical fitness of sports extracurricular students at SMAN 1 Surade stated that they were in the